2015
DOI: 10.1186/s12913-015-1032-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of antiretroviral treatment (ART) care service provision in Tigray Region health centers, North Ethiopia

Abstract: BackgroundClient satisfaction is a vital component and main concern intertwined with strategic decisions in service provisions. To improve efficiency of services, eliciting the opinion of users about the available services and identifying factors associated with dissatisfaction is very critical. Thus, the main objective of this study was to assess the perceived levels of clients’ satisfaction with health services at ART clinic level in health centres of Tigray Region in Ethiopia.MethodsCross sectional study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 6 publications
7
21
1
Order By: Relevance
“…For patients who traveled more than 1 h from home to health centers, satisfaction decreased by 44% compared to those patients who traveled less than 1 h to get to antiretroviral therapy service health centers. This result was consistent with those of studies in the Tigray region and the public health facility of the Sidama zone of Ethiopia [16,22]. The possible explanations might be the fact that long-distance travel is often associated with increased financial expenditure and absence from work and school.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For patients who traveled more than 1 h from home to health centers, satisfaction decreased by 44% compared to those patients who traveled less than 1 h to get to antiretroviral therapy service health centers. This result was consistent with those of studies in the Tigray region and the public health facility of the Sidama zone of Ethiopia [16,22]. The possible explanations might be the fact that long-distance travel is often associated with increased financial expenditure and absence from work and school.…”
Section: Discussionsupporting
confidence: 91%
“…Patients satisfaction measurement had important implications for services providers and planners to identify gaps and improvement of service quality of the health care system. However, this finding was lower than results of health centers in Tigray region, Ethiopia (89.6%) [22], Addis Ababa public hospitals (85.5%) [24], Sidama hospital, southern Ethiopia (85.5%) [15], and Bamenda-Cameroon 91.2% [19]. The reason could be the differences in the study setting, socio-demographic characteristics, and service units.…”
Section: Discussionmentioning
confidence: 61%
“…31 Similarly, a patient satisfaction survey conducted in Singapore, Tigray, and Jimma on clients’ satisfaction with ART services showed that the courtesy and respect displayed by health professionals have a positive impact on patient satisfaction; in this regard, most of the questions on level of satisfaction regarding the skill, attitude, and interaction of ART staffs were answered positively. 25 , 26 , 34 The result can be attributed to different reasons; the major reason could be due to the better attention given by Federal ministry of health and regional health bureau and existence of nongovernmental organizations specifically working on ART care such as Management Sciences for Health, Pharmaceuticals Fund and Supply Agency, and System for Improved Access to Pharmaceuticals and Services. Almost all (94.1%) the study participants were satisfied with the availability of required ART medications.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported by studies conducted in Kenya and Tigray. 25 , 33 The higher level of satisfaction among the illiterate and married respondents could be associated with lesser understanding of the significance of details of the functions in the pharmacy and the services they deserved to get.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation